Computational aerodynamics of hovering helicopter rotors - Nik Mohd., Nik Ahmad Ridhwan (Penerbit UTM, 2012)
The computation of rotor flowfields is a challenging problem in theoretical aerodynamics and essential for rotor design. In this paper we discuss the prediction of rotor hover performance, wake geometry and its strength using CFD methods. The benefits and differences between simple, momentum-based source-sink models and truncated vortex-tube far-field boundary conditions on the rotor flowfield modelling, and the convergence of the numerical solution are investigated and presented. Helicopter rotors in axial flight are simulated using the Helicopter Multi-block (HMB2) solver of the Liverpool University for a range of rotor tip speeds and collective pitch settings. The predicted data were then compared with available experimental data and the results indicates that, blade loading and wake geometry are in excellent agreement with experiments and have moderate sensitivity to the grid resolution. The work suggests that efficient solutions can be obtained and the use of the momentum theory is essential for efficient CFD computations.